Enhanced control of oncolytic measles virus using microRNA target sites - Leber, Mathias Felix; Bärtsch, Marc-Andrea; Anker, Sophie; Singh, Hans Martin; Bossow, Sascha; Engeland, Christine Elisabeth; Springfeld, Christoph; Jäger, Dirk; Kalle, Christof von; Ungerechts, Guy (Molecular therapy. Oncolytics, 2018)
Measles viruses derived from the live-attenuated Edmonton-B vaccine lineage are currently investigated as novel anti-cancer therapeutics. In this context, tumor specificity and oncolytic potency are key determinants of the therapeutic index. Here, we describe a systematic and comprehensive analysis of a recently developed post-entry targeting strategy based on the incorporation of microRNA target sites (miRTS) into the measles virus genome. We have established viruses with target sites for different microRNA species in the 3′ untranslated regions of either the N, F, H, or L genes and generated viruses harboring microRNA target sites in multiple genes. We report critical importance of target-site positioning with proximal genomic positions effecting maximum vector control. No relevant additional effect of six versus three miRTS copies for the same microRNA species in terms of regulatory efficiency was observed. Moreover, we demonstrate that, depending on the microRNA species, viral mRNAs containing microRNA target sites are directly cleaved and/or translationally repressed in presence of cognate microRNAs. In conclusion, we report highly efficient control of measles virus replication with various miRTS positions for development of safe and efficient cancer virotherapy and provide insights into the mechanisms underlying microRNA-mediated vector control.